2014
DOI: 10.1186/1472-6963-14-249
|View full text |Cite
|
Sign up to set email alerts
|

How nurses and their work environment affect patient experiences of the quality of care: a qualitative study

Abstract: BackgroundHealthcare organisations monitor patient experiences in order to evaluate and improve the quality of care. Because nurses spend a lot of time with patients, they have a major impact on patient experiences. To improve patient experiences of the quality of care, nurses need to know what factors within the nursing work environment are of influence. The main focus of this research was to comprehend the views of Dutch nurses on how their work and their work environment contribute to positive patient exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
309
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(335 citation statements)
references
References 31 publications
16
309
0
10
Order By: Relevance
“…Accordingly, the education of patients with diabetes has gained more importance for the control of the disease [2,3]. The health education given on the chronic diseases increases the patient autonomy and feeling of confidence, while it decreases the complications and cost [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the education of patients with diabetes has gained more importance for the control of the disease [2,3]. The health education given on the chronic diseases increases the patient autonomy and feeling of confidence, while it decreases the complications and cost [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses participating in this study prefer individual diabetes education. Individual patient education has several advantages such as having more time for the patient, but the group education is frequently assessed in the literature in terms of improving the diabetes results and developing the problem-solving skills in patients [17,20].…”
Section: Discussionmentioning
confidence: 99%
“…[6,22,23] The current study findings concur with other studies which found that lack of career development opportunities, especially opportunities for further education was one of the causes of relatively high nursing staff turnover in Japan and other high resource countries. [9,22] Some participants spoke of "being ordered" to do, having to adopt an unquestioning attitude, and having to learn unwritten rules, one of which was "understanding their place" in a hospital hierarchy. This meant that there were predictable ways of behaving and anticipated outcomes if the rules were not followed.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Satisfaction and commitment directly influence the RN's choices to stay or leave the institution. [3,9] Direct predictors of dissatisfaction and turnover include work overload and work stress, [1,5] whereas a supportive nursing management and favourable work group climate are predictive of staff retention. [4,9,10] In Africa, advancement opportunities and organizational characteristics associated with empowerment and autonomy have been found to decrease the likelihood of staff attrition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation